Effects of combinational treatment with ethephon and gibberellic acid on rice seedling growth and carbohydrate mobilization in seeds under ﬂooded conditions. (2nd October 2018) - Watanabe, Hajime; Honma, Kae; Adachi, Yusuke; Fukuda, Akari
ABSTRACT: Early seedling growth, including seedling emergence and vigor, is crucial in direct seeded rice. In this study, we examined the effects of gibberellic acid (GA3 ) and ethephon (ET) on the early growth of direct seeded rice, and on α-amylase activity and soluble sugar content in the seeds. Rice seeds were treated with water (control), ET, GA3, or ET+ GA3 and were allowed to grow for 21 days. The results showed that ET and GA3 synergistically improved the lengths of mesocotyl, coleoptile, mesocotyl+ coleoptile, and first leaf. Moderate synergistic effects of ET and GA3 were detected in the second and third leaves. ET+ GA3 treatment induced higher α-amylase activities during early post-germination growth, which is consistent with the longer coleoptile, mesocotyl, mesocotyl+ coleoptile, and first leaf. In addition, ET+ GA3 induced higher α-amylase activity in the seeds, and consequently, higher sucrose and glucose concentrations than other treatments. These results partially explain the regulatory mechanism underlying the synergistic interaction of ET and GA3 on rice seedling growth in terms of starch and sugar metabolism in the seeds, and this knowledge is expected to facilitate the practical use of ET and GA3 in direct seeded rice systems.